Evaluation of disease outcome with demographic,clinical and laboratory features of childhood-onset systemic lupus erythematosus: Single center experience (Annals of Medical Research, 2021)
Aim: To report demographic, clinical and laboratory findings with clinical outcome in childhood-onset systemic lupus erythematosus (cSLE)Material and Methods: Charts of all children with cSLE followed at pediatric rheumatology clinic of Gaziantep University between 2000-2016 were reviewed. Demographic data, history, age at diagnosis, physical examination, laboratory investigations, diagnostic criteria, follow-up duration and all therapeutic regimens were noted. The pediatric adaptation of the Systemic Lupus International Collaborating Clinics American College of Rheumatology Damage Index (PedSDI) has been used to evaluate the disease outcome.Results: The study population was consisted of 39 patients, 31 girls and 8 boys who were under 18 years at the time of diagnosis. Female: male ratio was 4.7:1. The mean age at disease onset was 10.5±4.56 years, and the mean follow-up duration was 26.4± 17.8 months. At the end of the follow-up period, fifteen patients (38.5%) had accrued damage (PedSDI≥1). We observed that renal, neuropsychiatric and musculoskeletal damage was the most frequent types of damage (38.5%). The damage score was higher in patients having increased number of diagnostic criteria at presentation (p:0.001).Conclusion: Although our study showed less damage index than patients from other countries, it has been well known that the damage accrual in SLE is higher in long term period, and mean follow-up period of our patients is lower than previous reports. We conclude that damage mainly affects renal, neurophyschiatric and musculoskeletal systems, and increased number of diagnostic criteria at presentation may cause much more damage.
Keywords: Children; disease outcome; systemic lupus erythematosus